Indian philosophy : an introduction to Hindu and Buddhist thought - King, Richard, 1966- (Edinburgh University Press, 1999)
What is Indian Philosophy? Why has India been excluded from the history of philosophy? Richard King provides an introduction to the main schools of Hindu and Buddhist thought, emphasising the living history of interaction and debate between the various traditions. The book outlines the broad spectrum of Indian philosophical schools and questions prevailing assumptions about the 'mythical', ahistorical and 'theological' nature of Indian thought. -- Provided by publisher.